Development of a Web Based Academic Supervision Application (SUAMIC) in Elementary Schools - Rhistiani, Yuanita; Kusumaningsih, Widya; Nurkolis (Tadrib: Jurnal Pendidikan Agama Islam, 2025)
This research focuses on the development of a web-based academic supervision application (SUAMIC) to enhance the efficiency, effectiveness, and transparency of academic supervision in elementary schools within the Ungaran Barat sub-district, Semarang Regency. The study follows the 4D model (Define, Design, develop, and disseminate), beginning with a needs analysis to identify challenges in the manual academic supervision process. The development process resulted in the SUAMIC application, which includes features such as user management, academic supervision via Google Forms, supervision recaps, and communication tools like Zoom and Live Chat. The validity of the SUAMIC application was assessed by content and media experts, both of whom deemed it feasible for use in academic supervision. Practicality testing conducted on a small scale and a large scale revealed high usability scores, confirming the application’s ease of use. Additionally, effectiveness was measured through pre-test and post-test results, with significant improvements in teachers' academic supervision skills. These findings demonstrate that SUAMIC effectively supports academic supervision and enhances teachers’ ability to manage and evaluate academic performance. In conclusion, the SUAMIC application provides a structured, systematic, and efficient way to conduct academic supervision, improving transparency and feedback in real-time. The study recommends integrating SUAMIC into school systems, providing training for users, and adding new features for further optimization. The findings suggest that SUAMIC can be a model for digitizing academic supervision and promoting educational reform in elementary schools.